Pathological Tumor Response Following Immune Checkpoint Blockade for Deficient Mismatch Repair Advanced Colorectal Cancer. (5th June 2020) - Ludford, Kaysia; Cohen, Romain; Svrcek, Magali; Foo, Wai Chin; Colle, Raphael; Parc, Yann; Thomas, Jane Varkey; Morris, Van Karlyle; Kopetz, Scott; Chang, George J; Overman, Michael; Andre, Thierry
Abstract: Immune checkpoint inhibition (CPI) for metastatic colorectal cancer (mCRC) with deficient mismatch repair (dMMR) demonstrates high clinical activity that appears durable, but the impact of CPI on pathological tumor response is unknown. In this retrospective analysis, our objective was to assess pathological response and clinical outcomes in dMMR mCRC patients treated with CPI prior to surgical resection of primary and/or metastatic tumor. Among 121 advanced dMMR mCRC patients treated with CPI at 2 institutions between November 2016 and December 2018, 14 underwent surgery. Pathologic complete response was noted in the resected specimens of 13 patients despite the presence of residual tumor on preoperative imaging in 12 of those patients. With median follow-up of 9 months, no patients have had disease relapse or progression. For this small retrospective study, the data suggest that residual radiographic tumor may not require systematic resection following response to anti-PD1–based therapy. However, larger prospective studies are warranted.